PENGGUNAAN METODE PENDEKATAN KETRAMPILAN PROSES UNTUK MENINGKATKAN AKTIVITAS HASIL BELAJAR IPA SISWA KELAS III SEKOLAH DASAR - Ernawati M (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The background of this research is the low of science study result of third grade student of SD Negeri 011 Kundur, to overcome the problem, the researcher conduct research with the aim to improve the low value of IPA through the application of method skill approach method. This type of research is a classroom action research (PTK). The learning process consists of several stages: planning, implementation, observation, and reflection. The result of research indicates that the learning result has an increase in the average prasiklus of student learning outcomes is 67,37 with total number of students who complete 14 people. In the first cycle increased by an average of 74.59 with a total of 19 students. In the second cycle increases with the average grade grade of 92.59 with a total number of students who completed 25 people.